Recruitment and management in local government authorities of Tanzania: A case of Masasi district council - Mboyi, Wishega (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of the degree of Master of Science in Human Resource Management (MSc-HRM) of Mzumbe University Dar es Salaam Campus College